2021
DOI: 10.21608/mnj.2021.213171
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Patternas Determinant of Overweight and Obesity among Young Adults

Abstract: Introduction:The prevalence of overweight and obesity are in continuous increasement all over the world. The management of obesity focuses on physical activity and healthy diet. Aim:the present study aimed at studying the lifestyle pattern as determinant of overweight and obesity among young adults.Method:Abaseline assessment survey study designwas utilized to accomplish this study. Convenience sampling technique was used to recruit total number of 132 young adults, who were invited through World Wide Web (WWW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…Most participants agreed that the program was easy to navigate and delivered at a logical and manageable pace. Similar results were found in a study conducted in Egypt, which concluded that HCPs were receptive to web-based delivery of intervention content [ 28 ]. Our study’s findings are consistent with existing literature [ 17 , 40 , 44 , 47 49 ], further supporting the acceptability and effectiveness of the training programs in improving nurses’ competencies.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Most participants agreed that the program was easy to navigate and delivered at a logical and manageable pace. Similar results were found in a study conducted in Egypt, which concluded that HCPs were receptive to web-based delivery of intervention content [ 28 ]. Our study’s findings are consistent with existing literature [ 17 , 40 , 44 , 47 49 ], further supporting the acceptability and effectiveness of the training programs in improving nurses’ competencies.…”
Section: Discussionsupporting
confidence: 87%
“…Most participants agreed that the program was easy to navigate and delivered at a logical and manageable pace. Similar results were found in a study conducted in Egypt, which concluded that HCPs were receptive to web-based delivery of intervention content [28]. Our study's findings…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…Weight gain then continues until middle age. ( 9) Obesity is a complex condition in which excess body fat increases the risk of hypertension, diabetes, metabolic syndrome, stroke, certain cancers, dyslipidemia, gallbladder disease, sleep apnea, osteoarthritis, and all may cause increased mortality, emotional distress, and social stigmatization (10) and is a major contributor to the global burden of chronic disease and disability. (11).…”
Section: Introductionmentioning
confidence: 99%
“…It can affect a person's health and well-being. (9) Overweight and obesity are among the most preventable causes of morbidity and mortality, and are the fifth leading cause of death worldwide. To take appropriate measures to manage overweight and obesity, it is important to examine an individual's lifestyle patterns, eating patterns, and physical activity, which may be the most common causes of this problem.…”
Section: Introductionmentioning
confidence: 99%